Peran Kaum Awam dalam Pengembangan Iman Gereja di Kota Malang - Lumbantoruan, Sopan R. (Perspektif, 2018)
Malang is a city which is always on its development. As the city is developing, so the life of the church is also ever-changing. The question would be: “Is the change of Christian faith on its way for better or for worse?” The writer tries to discern the question through field research among the faithful Christians in the city. As the sample, the writer has chosen a group of Christians within St. Andrew Parish, namely the St. Paul neighbourhood. The findings have been reflected referring to some source books as well as Church’s documents and lay spirituality. The writer concludes that involvement of lay people has great contribution to, even determines the whole life of the church.